Bridge 47 Target 4.7 Roadmap - 4.7, Bridge (Revista de Fomento Social, 2020)
Publication typology: Advocacy tool. Responsibility: Bridge 47. Author(s): Bridge 4.7 (with contributions of the participants of the Envision 4.7 Event, Helsinki, 6–7 November 2019). Language: English. Publication date: November 2019. Pages: 4. Acess: https://www.bridge47.org/node/241